Accumulation and clearance of α-synuclein aggregates demonstrated by time-lapse imaging - Opazo Dávila, Luis Felipe; Krenz, Antje; Heermann, Stephan; Schulz, Jörg B.; Falkenburger, Björn (Journal of neurochemistry, 2008)
Aggregates of α-synuclein are the pathological hallmark of sporadic Parkinson’s disease (PD), and mutations in the α-synuclein gene underlie familial forms of the disease. To characterize the formation of α-synuclein aggregates in living cells, we developed a new strategy to visualize α-synuclein by fluorescence microscopy: α-synuclein was tagged with a six amino acid PDZ binding motif and co-expressed with the corresponding PDZ domain fused to enhanced green fluorescent protein (EGFP). In contrast to the traditional approach of α-synuclein-EGFP fusion proteins, this technique provided several-fold higher sensitivity; this allowed us to compare α-synuclein variants and perform time-lapse imaging. A C-terminally truncated α-synuclein variant showed the highest prevalence of aggregates and toxicity, consistent with stabilization of the α-synuclein monomer by its C-terminus. Time-lapse imaging illustrated how cells form and accumulate aggregates of α-synuclein. A substantial number of cells also reduced their aggregate load, primarily through formation of an aggresome, which could itself be cleared from the cell. The molecular chaperone Hsp70 not only prevented the formation of aggregates, but also increased their reduction and clearance, underlining the therapeutic potential of similar strategies. In contrast to earlier assumptions build-up, reduction and clearance of α-synuclein aggregation thus appear a highly dynamic process.